The effect of bolus consistency on swallowing function measured by high‐resolution manometry in healthy volunteers. (14th June 2016) - Lan, Yue; Xu, Guang‐qing; Yu, Fan; Lin, Tuo; Jiang, Li‐sheng; Liu, Feng
Abstract : Objectives/Hypothesis: This study evaluated the effects of three levels of bolus consistency (water, thick liquid, and paste) on the nature and duration of physiologic pressure while swallowing in healthy adults using high‐resolution manometry (HRM). Study Design: A case series of healthy adults. Methods: Thirty‐four healthy young adults (mean age: 24.29 years) were instructed to swallow 3 mL and 10 mL of water, thick liquid, and paste material, respectively, during which the upper esophageal sphincter (UES) and pharyngeal pressures were measured by HRM. Variables that included maximum pharyngeal pressure, duration of pharyngeal pressure, pharyngeal pressure rise rate, UES residual pressure, duration of UES relaxation, and maximum preopening as well as postclosure UES pressure were analyzed across the three bolus consistencies by one‐way repeated measures analysis of variance. Results: Maximum pharyngeal pressure, duration of pharyngeal pressure, duration of UES relaxation, maximum preopening UES pressure, and maximum postclosure UES pressure were significantly increased while swallowing water when compared with the thick liquid and paste materials. No significant differences were observed in UES residual pressure and pharyngeal pressure rise rate among the three different consistencies. Conclusion: Variations in bolus consistency appear to have a significant effect on physiologic pressure and duration in healthy adults while swallowing water when compared with thicker materials. Identification of the differences across various bolus consistencies could provide further insight into the pathophysiology of both normal and pathological swallowing. Level of Evidence: 4. Laryngoscope, 127:173–178, 2017